INTERVENTION OF 5-FINGER HYPNOTIC RELAXATION TECHNIQUE IN COMPREHENSIVE MIDWIFERY CARE FOR FOR A MULTIPAROUS WOMAN WITH PREGNANCY-RELATED ANXIETY - Wardany, Marzita; Nursifa, Niknik; Sri Mujiwati; Sri Lestari, Endah (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2024)
During the third trimester of pregnancy, women often experience various discomforts, including anxiety. One non-pharmacological treatment to alleviate this anxiety is the Five-Finger Hypnosis technique. At Clinic "A" in 2023, out of 143 pregnant women, 50 in the third trimester reported experiencing anxiety. This study aims to evaluate the effectiveness of midwifery care using the Five-Finger Hypnosis technique to reduce anxiety in third-trimester pregnant women. Data collection methods included interviews, observations, and documentation review. The subject of this study was Mrs. "L," a G1P0A0 patient at 35 weeks and 6 days of gestation, who reported anxiety during pregnancy. The results showed that comprehensive midwifery care was conducted normally without complications. Mrs. "L" received the Five-Finger Hypnosis intervention six times: on the first day of her clinic visit and again on the 3rd, 6th, 8th, 11th, and 14th days following her initial visit. After these sessions, her anxiety significantly decreased, and she reported feeling more comfortable and relaxed. This study concludes that comprehensive midwifery care, including the Five-Finger Hypnosis technique, was effective in reducing anxiety for Mrs. "L." Such care can be beneficial in minimizing potential complications during pregnancy, childbirth, the newborn period, postpartum, and contraceptive services. Keywords: Anxiety, 5 finger hypnosis, Midwifery care